1989
DOI: 10.1007/bf00844751
|View full text |Cite
|
Sign up to set email alerts
|

Coping styles, paradox, and the cold pressor task

Abstract: The study investigated how coping style differences affected performance on the cold pressor task. Reactions of "monitors" (individuals who prefer having information about stressors) and "blunters" (individuals who avoid cues connected with stressors) were compared, using different instructional sets. The study also assessed the effectiveness of paradoxical intention compared to more traditional cognitive strategies. Monitors and blunters were identified using Miller's recently developed Behavioral Style Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 31 publications
1
28
2
Order By: Relevance
“…ies, the research has shown that those identified as high monitors or low blunters by the scale typically use information-seeking strategies under threat whereas those identified as low monitors or high blunters typically use distracting strategies [5,16,21]. Findings consistent with this have been obtained with medical populations.…”
Section: Evidence On Coping Stylesmentioning
confidence: 63%
“…ies, the research has shown that those identified as high monitors or low blunters by the scale typically use information-seeking strategies under threat whereas those identified as low monitors or high blunters typically use distracting strategies [5,16,21]. Findings consistent with this have been obtained with medical populations.…”
Section: Evidence On Coping Stylesmentioning
confidence: 63%
“…Recent studies have treated Monitoring and Blunting as orthogonal (Miller et al, 1988 and have used median splits on both scales to identify high versus low Monitors and high versus low Blunters (Miller, 1987;Miller et al, 1988Miller et al, , 1989. Other studies (Efran et al, 1989;Miller and Mangan, 1983;Steketee et al, 1989) have used the difference between Monitoring and Blunting scores to create median splits, with high scorers being classified as Monitors and low scorers being classified as Blunters. A problem with the latter method is that individuals either high on both scales or low on both scales would tend to be classified as Blunters.…”
Section: Discussionmentioning
confidence: 96%
“…By contrast, soldiers with mild SEDOAD demonstrated a greater inclination to avoid asthmarelated information. The presumably decreased need to be attuned to their illness [24] might have decreased the anxiety and concern of these soldiers, enabling them to be better geared towards improving their overall functioning and quality of life.…”
Section: Variablementioning
confidence: 97%
“…When individuals are faced with an aversive event, their approach towards it can vary along two dimensions, monitoring and blunting [23,24]. Monitoring reflects the extent to which the individual actively chooses to seek information about the nature of an event, and is alert and sensitized to this event.…”
Section: Instrumentsmentioning
confidence: 99%